Research on Novel Hybrid Torque Sharing Function for Switched Reluctance Motors - Fahad Al-Amyal; Laszlo Szamel (IEEE Access, 2022)
Torque Sharing Function (TSF) approach can be considered a promising method to solve the torque ripple issue in switched reluctance motors (SRMs) drives at low and medium speed ranges. However, at the high-speed operation of the machine, the actual phase current fails to track the reference current profile. This limitation primarily occurs over the demagnetization period of each phase current. Consequently, each phase torque will also fail to track its corresponding reference torque created by the TSF strategy. As a result of the torque tracking error, a considerable torque ripple will be produced. To address this issue, a novel hybrid TSF is proposed in this research article. The hybrid TSF can adapt during the real-time operation relying on the current (and thus the torque) tracking capability during the magnetization period, which is much higher than during the demagnetization period. At each electrical cycle, the rising part of the incoming phase torque reference is re-profiled to mirror the declining part of the actual torque of the outgoing phases. And therefore, the torque tracking error can be compensated, and a remarkable torque ripple suppression will be attained. Additionally, within the hybrid TSF, an overlap angle controller is also proposed in this work and participated in high-speed operation. The controller keeps monitoring the error between the commanded torque and the actual average torque of the machine, and by adjusting the overlap angle in real-time, the error can be further compensated. Thus, further torque tracking capability is attained. A set of simulation results are presented and favorably compared with other traditional TSF approaches to demonstrate the feasibility and validity of the proposed hybrid TSF.